Italian Acquisitions In Russia: Cultural Impact in the Post-Acquisition Integration Process - Tocchio, Andrea (My University, 2015)
Moving into a foreign country through FDI implies the choice between M&A or greenfield investment. For what concern M&A, they are made up of several steps, starting with the engagement with the target, the subsequent negotiations till the signature of the deal. Once the acquisition process is over, the integration process starts: it is made up of two distinct, but intertwined processes of task and human (or sociocultural) integration. The first is concerned with the activities and operations performed, the second with socialising and enhancing participation of employees. Culture differences played a relevant role in the integration process, but their effects are not so clear and the findings referring to the relationship between culture and outcomes of acquisition are inconclusive. For these reasons, the present study proposes a framework in which the role of cultural impact is highlighted. Its influence on task and human integration is presented, according to different post-acquisition integration strategies adopted. The study is based on 3 semi-structured interviews with managers in charges during the integration process of Italian acquisitions in the Russian Federation. Questions about the choice of the country, issues with authorities and legislation, reasons for the choice of the target acquired, steps of the acquisition process, subsequent integration process and performance evaluation are presented. Findings show how national and organisational culture impact on the integration process, especially on the human side, due to the strategy adopted.
Keywords: M&A; Italy; Russia; integration process; cultural impact; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|; fi=Organisaatioiden viestintä|en=Communication in organizations|